Effects of Ginsenoside Rf on dextran sodium sulfate-induced colitis in mice - Ahn, Sungeun; Simu, Shakina Yesmin; Yang, Deok-Chun; Jang, Mi; Um, Byung-Hun (TAYLOR & FRANCIS LTD, 2021)
Inflammatory bowel disease (IBD) is a critical disorder characterized by chronic inflammation of the gastrointestinal tract, primarily the small intestine and colon, which eventually leads to disruption of the gut barrier function. Panax ginseng (P. ginseng) is an important traditional herb, which contains various active constituents known as ginsenosides. Ginsenoside Rf (Rf) is a dynamic component of P. ginseng and is rarely available in other species. This study determined the anti-inflammatory effects of Rf in a dextran sodium sulfate (DSS)-induced colitis mouse model. The results demonstrated significantly lower body weight loss and shortening of colon length in mice treated with Rf than in DSS-treated mice. In addition, inflammatory signalling mechanisms involving interleukin-6 and tumour necrosis factor-alpha were inhibited in Rf-treated mice. The results suggest Rf as a potential anti-inflammatory agent that can be used for the treatment of IBD.
Keywords: INFLAMMATORY-BOWEL-DISEASE; MEDICINAL-PLANTS; NATURAL-PRODUCTS; PANAX-GINSENG; KAPPA-B